The Development of Science Teaching Materials Based on Android Mobile to Improve Critical Thinking Skills in Junior High School Students - Nurul Iqdami Zuniari; Sri Wahyuni Wahyuni; Zainur Rasyid Ridlo (Universitas Syiah Kuala, 2023)
The development of science teaching materials based on android mobile is based on the need for teaching materials that are suitable for 21st-century learning which is synonymous with the use of technology, information, and communication. This research aims to know the validity, practicality, and effectiveness of science teaching materials based on android mobile in improving students' critical thinking skills. The manufacture of teaching materials also aims to improve the low critical thinking skills of junior high school students. The research conducted is development research with the ADDIE development model. The subject of the study was a grade 7A student of SMPN 2 Maesan, Bondowoso. This study used instruments in the form of validation sheets, practicality sheets, and critical thinking skill tests. Data analysis techniques used in research consist of validity test analysis, practicality test analysis, and effectiveness test analysis. The results showed that (1) the percentage of validity of science teaching materials based on android mobile is 92% of the average of three validators, (2) the percentage of the practicality of science teaching materials based on android mobile is 86%, (3) the effectiveness score of science teaching materials based on android mobile 86%, (4) the effectiveness score of science teaching materials based on android mobile is 0.69 obtained from the N-gain test and 75% from the student response questionnaire so that it can be concluded that science teaching materials based on android mobile are valid, practical and effective for improving the critical thinking skills of junior high school students.